2020
DOI: 10.5897/ajpac2019.0812
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of kinetics and equilibrium studies of biosorption potentials of bamboo stem biomass for removal of Lead (II) and Cadmium (II) ions from aqueous solution

Abstract: The discharged of lead and cadmium above maximum permissible limits into surface water and environment without any pre-treatment methods has caused severe heath challenges to humanity. In other to minimize the reoccurrence, this research aim to ascertain biosorption capacity of bamboo stem biomass to remove lead and cadmium from aqueous solution. Batch experiment and data evaluation under optimum removal conditions (such as pH, contact time, temperature, biosorbent dosage, initial heavy metal concentration) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 42 publications
2
2
0
Order By: Relevance
“…Increasing the temperature can reduce the adsorption powers between the adsorbate and the adsorption destinations on the biomass surface, causing a reduction in the adsorption limit. This phenomenon is observed in the results presented in this study, as well as in others when using various biomasses such as bamboo stems (Akinyeye et al, 2020), microalgae Parachlorella sp. (Dirbaz & Roosta, 2018), and Aphanothece sp.…”
Section: Removal Of CD 2+supporting
confidence: 88%
See 1 more Smart Citation
“…Increasing the temperature can reduce the adsorption powers between the adsorbate and the adsorption destinations on the biomass surface, causing a reduction in the adsorption limit. This phenomenon is observed in the results presented in this study, as well as in others when using various biomasses such as bamboo stems (Akinyeye et al, 2020), microalgae Parachlorella sp. (Dirbaz & Roosta, 2018), and Aphanothece sp.…”
Section: Removal Of CD 2+supporting
confidence: 88%
“…Thus, more cadmium ions escape from the solid phase, according to what was reported by Cherik & Louhab (2018) and Naseem et al (2019). It has been found that at high temperature, the thickness of the boundary layer decreases due to the expanded inclination of the metallic particle to escape from the surface of the biomass to the disposition stage, which causes a decrease in adsorption as the temperature increases (Akinyeye et al, 2020). Increasing the temperature can reduce the adsorption powers between the adsorbate and the adsorption destinations on the biomass surface, causing a reduction in the adsorption limit.…”
Section: Removal Of CD 2+supporting
confidence: 58%
“…The Freundlich isotherm depends on the interaction between adsorbed ions. It is expressed as by equation (5).…”
Section: Adsorption Isothermmentioning
confidence: 99%
“…With the aim of addressing sustainable development and environmental pollution, researchers around the world proposed and implemented several pollution reduction methods. Existing water treatment technologies adopted for the removal of Arsenic include oxidation, chemical settling, exchange of ions, adsorption, separation of membrane, electrodialysis, coagulation-precipitation and reverse osmosis etc (17)(18)(19)(20). Due to their high energy demand, low efficiency in metal removal, generation of sludge, high capital cost, expensive maintenance, membrane replacement and chance of clogging etc (21)(22)(23), there is a high demand for simple, versatile technology that will help in cost process.…”
Section: Introductionmentioning
confidence: 99%